Association of adenotonsillar disease and adenotonsillectomy with the development of vitiligo: A nationwide population-based cohort study - Kim, Jong Seung; Lee, Min Gyu; Lee, Sang-Kyung; Yeom, Sang-Woo; Kang, Min-Gu; Lee, Jong Hwan; Lee, Il-Jae; Park, Jin; Yun, Seok-kweon; Nam, Kyung-Hwa (Frontiers in Medicine, 2022)
Backgrounds: Vitiligo is a common acquired skin depigmentation disorder and is associated with various other autoimmune diseases including thyroid disease and rheumatoid arthritis. Similarly, adenotonsillar disease (ATD) may induce inflammatory or autoimmune diseases in other organs including the skin. However, the influence of ATD on the development of vitiligo has not been studied. Objectives: To determine the association between ATD and adenotonsillectomy, and the development of vitiligo Design & Methods: Using data from the National Health Insurance Service database, patients diagnosed with ATD between 2008 and 2010 were included in the study. We performed two-rounds of 1:1 propensity score matching in the ATD and adenotonsillectomy groups. The ATD and non-ATD groups both included 206,514 individuals. Among the ATD group, the adenotonsillectomy and non-adenotonsillectomy groups both included 23,354 individuals. Each individual was monitored until 2019. Primary endpoint was the risk of vitiligo. Using the Cox Proportional Hazards model, the incidence of vitiligo and the hazard ratio (HR) were calculated. Results: The incidence of vitiligo was 1.16-fold higher in the ATD group than in the non-ATD group (adjusted HR [aHR], 1.16; 95% confidence interval [CI], 1.09–1.24) and 0.82-fold lower in the adenotonsillectomy group than in the non-adenotonsillectomy group (aHR, 0.82; 95% CI, 0.68–0.99). Additionally, the other risk factors for developing vitiligo included thyroid disease (aHR, 1.48; 95% CI, 1.11–1.98), age younger than 30 years (aHR, 1.18; 95% CI, 1.09–1.27), and age over 60 years (aHR, 1.22; 95% CI, 1.06–1.41), while factors including rural residency (aHR, 0.91; 95% CI, 0.85–0.98) and low economic status (aHR 0.87; 95% CI, 0.82–0.93) were related to decreased incidence of vitiligo. Conclusion: Herein, ATD increases the risk of vitiligo and adenotonsillectomy attenuate its development. Clinicians should consider ATD as a pathogenic factor for vitiligo and the potential effect of adenotonsillectomy in its management.